The Impact of Liquidity and Solvency Ratios on Profitability: Evidence From The Indonesian Construction Sector (2020-2023) - Arisandi F, Tb Daniel (Banking & Management Review, 2025)
Introduction/Main Objectives: The construction and building industry plays a vital role in Indonesia’s infrastructure development, encompassing roads, bridges, buildings, and other public facilities. Development in Indonesia, which includes the construction of roads, bridges, buildings and other public facilities. Background Problems: According to Indonesia’s GDP data from 2020 to 2023, the construction sector experienced a sharp decline in revenue in 2020 as a result of the COVID-19 pandemic. Although recovery began in 2021, financial performance among construction firms has remained uneven. Ensuring sound financial health is therefore essential for attracting investment. Novelty: Previous empirical evidence indicates inconsistencies in the relationship between financial ratios and Return on Assets (ROA), highlighting the need for further investigation. Research Methods: This study employs descriptive and verification methods within a quantitative framework. Data were obtained through purposive sampling of construction and building subsector companies listed on the IDX from 2020 to 2023, and were analyzed using multiple linear regression. Finding/Results: The findings reveal that the Current Ratio (CR) has a positive and significant effect on Return on Assets (ROA), while the Debt-to-Equity Ratio (DER) has a negative and significant effect on ROA. Together, these variables explain 63.9% of the variation in ROA, with the remaining 36.1% influenced by other factors. Conclusion: In conclusion, the Current Ratio (CR) positively contributes to financial performance, as measured by ROA, whereas the Debt-to-Equity Ratio (DER) exerts a negative effect. These findings underscore the importance of maintaining liquidity and managing leverage in construction and building subsector companies listed on the IDX.